Violence and discrimination among Ugandan residents during the COVID-19 lockdown - Elizabeth Katana; Bob Omoda Amodan; Lilian Bulage; Alex R. Ario; Joseph Nelson Siewe Fodjo; Robert Colebunders; Rhoda K. Wanyenze (BMC, 2021)
Abstract Background In March 2020, the World Health Organization (WHO) declared COVID-19 a pandemic. Many countries in Sub-Saharan Africa, Uganda inclusive, implemented lockdowns, curfew, banning of both private and public transport systems, and mass gatherings to minimize spread. Social control measures for COVID-19 are reported to increase violence and discrimination globally, including in Uganda as some may be difficult to implement resulting in the heavy deployment of law enforcement. Media reports indicated that cases of violence and discrimination had increased in Uganda's communities following the lockdown. We estimated the incidence and factors associated with experiencing violence and discrimination among Ugandans during the COVID-19 lockdown to inform control and prevention measures. Methods In April 2020, we conducted a secondary analysis of cross-sectional data under the International Citizen Project (ICP) to assess adherence to public health measures and their impact on the COVID-19 outbreak in Uganda. We analyzed data on violence and discrimination from the ICP study. We performed descriptive statistics for all the participants' characteristics and created a binary outcome variable called experiencing violence and/or discrimination. We performed logistic regression analysis to identify the factors associated with experiencing violence and discrimination. Results Of the 1726 ICP study participants, 1051 (58.8%) were males, 841 (48.7%) were currently living with a spouse or partner, and 376 (21.8%) had physically attended work for more than 3 days in the past week. Overall, 145 (8.4%) experienced any form of violence and/or discrimination by any perpetrator, and 46 (31.7%) of the 145 reported that it was perpetrated by a law enforcement officer. Factors associated with experiencing violence or discrimination were: being male (AOR = 1.60 CI:1.10-2.33), having attended work physically for more than 3 days in the past week (AOR = 1.52 CI:1.03-2.23), and inability to access social or essential health services since the epidemic started (AOR = 3.10 CI:2.14-4.50). Conclusion A substantial proportion of Ugandan residents experienced violence and/or discrimination during the COVID-19 lockdown, mostly perpetrated by law enforcement officers. We recommend mitigation of the collateral impact of lockdowns with interventions that focus on improving policing quality, ensuring continuity of essential services, and strengthening support systems for vulnerable groups including males.